1963
DOI: 10.1128/jb.85.5.1094-1103.1963
|View full text |Cite
|
Sign up to set email alerts
|

CHARACTERISTICS OF CLOSTRIDIUM PERFRINGENS STRAINS ASSOCIATED WITH FOOD AND FOOD-BORNE DISEASE

Abstract: England, Europe, and Asia, associated with foodpoisoning outbreaks; 28 from the United States, associated with outbreaks or contaminated foods; and 25 from natural or pathological sources-have been studied to determine their serological relationships, sporulation and heat-resistance of spores, and their hemolytic activity on mammalian bloods. A comparison of the results obtained with these three groups of strains reveals that the Eurasian group is characterized by serological typability, poor sporulation with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
43
1

Year Published

1964
1964
1989
1989

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(50 citation statements)
references
References 10 publications
6
43
1
Order By: Relevance
“…In recent years Clostridium perfringens has emerged as a major cause of foodborne illness in the United States (Center for Disease Control [CDC] 1976). Considerable effort has been extended to determine its cultural characteristics (Angelotti et al 1962;Hall et al 1973;and Shahidi and Ferguson 1971). The commonly used procedures for the isolation of C. perfringens from food samples suspected to have caused foodborne illness include incubation at 46°C and the use of antibiotics to inhibit competitive organisms that may make up the normal flora of foods (Bacteriological Analytical Manual for Foods [ BAM] 1976).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years Clostridium perfringens has emerged as a major cause of foodborne illness in the United States (Center for Disease Control [CDC] 1976). Considerable effort has been extended to determine its cultural characteristics (Angelotti et al 1962;Hall et al 1973;and Shahidi and Ferguson 1971). The commonly used procedures for the isolation of C. perfringens from food samples suspected to have caused foodborne illness include incubation at 46°C and the use of antibiotics to inhibit competitive organisms that may make up the normal flora of foods (Bacteriological Analytical Manual for Foods [ BAM] 1976).…”
Section: Introductionmentioning
confidence: 99%
“…The role of Clostridiunz perfringens as a causative agent of food poisoning has received increasing attention in the last few years, particularly in the United States and England (Hobbs, 1962 ;Angelotti et al, 1962). Hall et al (1963), in a study of 53 strains of C. perfringens associated with cases of food poisoning in both countries, reported that the spores from the English strains were considerably more heat-resistant. It was suggested that cases of C. perfringens food poisoning in England came primarily from foods contaminated prior to cooking, and in the United States from food contaminated after cooking.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Strong et al (1963) have shown a rather high incidence of contamination of fresh meats with C. perfringens. Hall and Angelotti (1965) have also shown a high incidence of fresh meat contamination with C. perfrinyens, but found only a small percentage of these to produce heat-resistant spores. These studies, however, do not give any data on the survival of C. perfringens in hams.…”
Section: Introductionmentioning
confidence: 99%
“…The symptoms are first noticed S to 22 hr after ingestion of the food, and usually continue for less than 1 day. Hall et al (1963) reported that C. perJringens foodpoisoning outbreaks in the United States have been attributed to both heat-resistant and non-heat-resistant type A strains of the organism.…”
Section: Introductionmentioning
confidence: 99%
“…occasionally found C. perfrZtzgc*~s when searching for C. henzolyticum in the livers of apparently normal cattle. Kraneveld and Raden (1940) reported the finding of anaerobes in 26 of 50 bile specimens obtained from apparently healthy cattle from middle Java. Schweinburg and Sylvester (1953) bacteriologically examined tissues and organs of healthy dogs, rabbits, guinea pigs, rats, and hamsters.…”
Section: Introductionmentioning
confidence: 99%